Development of a set of bacterial engineered glycoconjugates as novel serogroup-specific antigens for the serodiagnosis of Escherichia coli O26, O111, O103 and O45 infections associated to hemolytic uremic syndrome - Ana J. Caillava; Luciano J. Melli; Malena Landoni; Stella Maris Landivar; Isabel Chinen; Alicia S. Couto; Marta Rivas; Juan E. Ugalde; Diego J. Comerci; Andrés E. Ciocchini (Microbial Cell Factories)
Abstract Hemolytic uremic syndrome associated to Shiga toxin-producing Escherichia coli infection (STEC-HUS) is a life-threatening condition characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney failure. Among STEC, E. coli O157:H7 is the dominant serotype related with human disease worldwide; however, a subset of STEC non-O157 serotypes -named the “Big-Six”- that include the E. coli serogroups O145, O121, O26, O111, O103 and O45 became of a great concern for their potential to cause HUS. Previously, we have demonstrated that serological tests based on bacterial engineered glycoconjugates developed by exploiting the Campylobacter jejuni N-glycosylation machinery, notably increases the association rate of HUS to O157, O145 and O121 STEC infections. In this work, we developed the recombinant glycoproteins O26-AcrA, O111-AcrA, O103-AcrA and O45-AcrA by co-expressing in E. coli the gene cluster required for the synthesis of the O polysaccharide corresponding to each serogroup, the C. jejuni oligosaccharyltransferase (OTase) PglB, and the carrier protein AcrA. The glycans attached to AcrA in the produced and purified glycoconjugates were characterized by mass spectrometry. The glycoconjugates were evaluated as antigens for detection of IgM antibodies against the O polysaccharide of the lipopolysaccharide of O26, O111 and O103 STEC strains in human serum samples. Our results demonstrate that O26-AcrA, O111-AcrA and O103-AcrA allow a clear discrimination between negative and positive samples obtained from patients with HUS associated to O26, O111 and O103 STEC infections. Additionally, these novel antigens are serospecific allowing E. coli serogroup identification which may contribute to the epidemiological surveillance of STEC-HUS patients and their contacts.